Entre licenciatura e bacharelado em Educação Física: reformas no ensino superior e a constituição de identidades dos profissionais de educação física da ESEF/UFPel - Finoqueto, Leila Cristiane Pinto (2013)
This study dealt with the impact caused by the latest syllabus reform in the Physical Education course (both in the Teaching and the Bachelor s Degrees) on the constitution of Physical Educators identities. The main objective of the research was to understand whether these changes were appropriate and how they affected the syllabus and College students identities. Post-structuralist studies, mainly Foucauldian ones, were taken as references to work on concepts such as discourse, discursive practices and power-knowledge. The use of Stephen Ball s Policy Cycle Approach made the analyses address a view on educational and syllabus policies which could be understood as the result of constant conflicts in different contexts that interpenetrate and relate to each other to yield global-local effects. The investigation was carried out by discourse analyses of: official texts in educational reform that aims at students pursuing teaching and bachelor s degrees in Physical Education; the faculty involved in the development of a political text in the country; and the faculty who focused on the re-contextualization of official norms in the local context of political production and of seniors who graduated at ESEF/UFPel in 2010. In this study, I have defended that the Syllabus Reform which was carried out in 2004 in Physical Education courses (CNE/CES Resolution no. 07/2004) potentized the discourse of distinction between both degrees. Thus, effective possibilities of thinking about the development and the constitution of distinct identities were created and consolidated. Even so, these identities were embedded in common discursive practices which showed performativity and managerialism as political technologies in the (self)development process. Besides, I have pointed out the weight of tradition which fits official norms without abandoning old pedagogical practices that ESEF/UFPel professors consider creative and adequate to the development processes of professionals in Physical Education. Finally, the work market is seen as an indicator and the end of professional development as well as the consolidation of studies which look at Physical Education from a biological perspective in terms of physical activity, performance and health.